Structural Equation Modelling to Measure Perceptions, Interests and Their Influence on Young People's Intention to Venture into Agriculture - Safitri, Husnul Ika; Muhaimin, Abdul Wahib; Nugroho, Tri Wahyu (Universitas Panji Sakti, 2024)
The declining number of farmers is a prominent problem in the agricultural sector. On the other hand, interest in engaging in agriculture, especially among the younger generation, has also declined. The younger generation tends to perceive working in agriculture as unprofitable. The young generation's intentions can be influenced by their perception and interest. This study aims to analyze the effect of young people's perceptions on interest and intention to work in the agricultural sector, analyze the effect of interest on intention and analyze the effect of perception on intention mediated by interest. The research was conducted in Jampet Village, Ngasem District, Bojonegoro Regency. A survey of 100 youths aged 15-35 in Jampet Village explored their perceptions and interests in agriculture through distributed questionnaires. Informants were determined using the purposive sampling method, and data were analyzed using the SEM method. In accordance with the test results, perception has a positive and significant influence on interest of 78.2% with a coefficient value of 0.782, and directly has a positive effect of 48.2% on the intention of the younger generation in business in agriculture; in addition, the interest variable also has a positive and significant influence of 46% on the intention of the younger generation to go directly into the agricultural sector. In comparison, the effect of perception on intention mediated by the interest variable shows positive and significant results of 35.9%.